2017
DOI: 10.1016/j.jval.2017.08.1168
|View full text |Cite
|
Sign up to set email alerts
|

Target Organ Damage And The Long Term Effect of Nonadherence To Clinical Practice Guidelines In Patients With Hypertension: A Retrospective Cohort Study

Abstract: Background. There was limited published data on target organ damage (TOD) and the effect of nonadherence to practice guidelines in Ethiopia. This study determined TOD and the long term effect of nonadherence to clinical guidelines on hypertensive patients.Methods. An open level retrospective cohort study has been employed at cardiac clinic of Gondar university hospital for a mean follow-up period of 78 months. Multivariate Cox regression was conducted to test associating factors of TOD. Results. Of the total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…This is attributed to some cultural and social taboos that prohibit transparency and disclosure to clinicians. These clinicians’ traditional trend should be replaced by the clinical guideline recommendations to change the prescribing practice for better patient outcomes since guideline recommendations are better supported by clinical evidence and superior to individual preferences …”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to some cultural and social taboos that prohibit transparency and disclosure to clinicians. These clinicians’ traditional trend should be replaced by the clinical guideline recommendations to change the prescribing practice for better patient outcomes since guideline recommendations are better supported by clinical evidence and superior to individual preferences …”
Section: Introductionmentioning
confidence: 99%
“…Peningkatan tekanan darah dalam waktu yang lama menyebabkan kerusakan struktur dan fungsi berbagai organ 3 . Organ vital yang sering mengalami kerusakan akibat hipertensi adalah jantung, otak, mata dan ginjal 4,5 .…”
Section: Pendahuluanunclassified
“…Kerusakan pada ginjal terjadi karena peningkatan tekanan glomerulus, peningkatan glomerulus filtration rate (GFR) dan kerusakan nefron 6,7 . Efek kerusakan ginjal akibat hipertensi dapat terjadi asimptomatik sampai dengan kerusakan ginjal terminal 5 .…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…During the 5 to 10 years of follow-up, less than 40% of p a t i e n t s c o n t i n u e d w i t h t h e i r p r e s c r i b e d antihypertensive treatment. (4,5).Other studies have reported numerous factors that affect adherence including lifestyle, psychological issues, health literacy, support systems and side effects of medications (6). This study was conducted in Buengkan province, which is the newest province of Thailand and is considered a rural area.…”
Section: Introductionmentioning
confidence: 99%